The investigation of batch-to-batch variabilities in the composition of isolates from fish and mammalian species using different protocols - Rýglová, Šárka; Braun, Martin; Suchý, Tomáš; Hříbal, Miloň; Žaloudková, Margit; Vištějnová, Lucie (Food research international (Ottawa, Ont.), 2023)
The aim of this study was to investigate batch-to-batch inconsistencies in the processing of pig and fish collagen isolates processed using two protocols that differed in terms of the acetic acid concentrations applied and the pre- and post-extraction steps, and which were previously tested in our laboratory with the intention of preserving the biological structures and functions of the collagen isolates for biomedical purposes. Both the major and minor components such as the amino acids, lipids, water, glycosaminoglycan and ash contents and elemental content, as well as the structure and morphology of the raw sources and the resulting batches of isolates were subsequently examined in detail applying standardized analytical methods including high perfomance liquid chromatography, ultraviolet-visible and infrared spectrometry, polyacrylamide gel electrophoresis, energy dispersive spectroscopy and scanning electron microscopy. All the fish isolates provided severalfold higher yields (8-45 wt%) than did the pig isolates (3-9 wt%). In addition, the variability of the fish isolate yields (the coefficient of variation for processing A: 16.4-32.9 % and B: 6.8-17.4 %) was significantly lower (p ≤ 0.05, n = 5) than that of the pig isolates (A: 27.7-69.8 %; B: 35.3-87.9 %). In general, the fish skin batches had significantly higher protein contents (˃60 wt%) and lower lipid contents (<10 wt%) than the pig skin batches (<55 wt% protein and up to 66 wt% lipid). In addition, the fish skin batches did not differ significantly in terms of their composition applying the same processing method, whereas the pig skin batches exhibited considerable variations in terms of their compositions, particularly regarding the protein and lipid contents. It can be stated that, concerning the fish isolates, processing B was, in most cases, slightly more efficient and reproducible than processing A. However, concerning the pig isolates, although processing A appeared to be more efficient than processing B in terms of the yield, it resulted in the production of isolates that contained a certain level of contaminants. The study provides a comprehensive discussion on the suitability of the processing protocol in terms of producing batches of reproducible quality according to the specific type of biomaterial processed from different animal species.
Keywords: kolagen; Lipids; Characterization; Swine; Batch variability; prasata; Fishes; lipidy; zvířata; Mammals; Green processing; ryby; Pig and fish skin; Waste treatment; savci; Collagen; Animals